Conservation practice in a multi-cultural society: A literature review towards incorporating stakeholders’ preferences in heritage management using Multi-Criteria Analysis - Wan Abdullah Zawawi, Noor Amila; Abdullah, Alias; Idrus, Arazi (2010)
The characteristics of multicultural society in Malaysia are ingrained in the built heritage of its early townships. Architectural details of traditional shophouses, which are the early urban settlements, are a rich mixture of Chinese, Indian, European and Malay cultures. Rapid development pace and escalating market values progressively replaces these buildings with newer and higher density structures. The current conservation practices, based on the mono-cultural British system, are in need of improvement to meet the needs and requirement of multicultural Malaysia. The first stage towards conservation management is identification of built heritage via an inventory exercise. The criteria and their priorities are defined by the inventory committee. The aim of this paper is to compare the criteria used to evaluate cultural heritage significance in various countries. Identification of heritage significance is an important exercise as it is the first step towards heritage conservation. As part of the efforts to ensure the heritage evaluation are more relevant to local condition, there should be improvement on technical services and resources for determining its significance based on appropriate values that suits multicultural Malaysia contexts. This paper is the first of two parts research paper on objective decision making framework in conservation practice. This first part focuses on conceptual framework for heritage listing criteria and stakeholders’ preferences. The comparison analysis is applied to determine difference in practice, leading to establishment of a set of evaluation criteria for heritage listing.